Manchester City’s Premier League Dominance: Longitudinal Study for 2021-2023 / Muhammad Zunnurain Nor Aza ... [et al.]. - Nor Aza, Muhammad Zunnurain; Ismail, Arisya; Esa, Muhammad Nabil; Abdul Harith, Anis Shafira; Mohamed, Muhamad Noor; Saiful Annur, Muhamad Safiq; Adnan, Mohd Aizzat (2024)
This study investigates the factors contributing to Manchester City Football Club’s sustained dominance in the Premier League between the 2020/21, 2021/22 and 2022/23 seasons. Employing a longitudinal research design, the study examines the interplay between tactical details and the effect of player changing towards tactical details in Manchester City throughout the 2020/21, 2021/22 and 2022/23 seasons. Key areas of analysis include Guardiola’s tactical philosophy, player recruitment and development, and the impact of player change. The sample size in this study was 114 matches (N = 114) of the English Premier League, and it was divided into three seasons, which are 2020/21, 2021/22 and 2022/23. Furthermore, the methodology used was notational analysis and secondary data. The data is collected from Premier League Official Apps. Besides, based on analysis conducted by Kruskal-Wallis, the findings showed there are significant differences in terms of the shot-off target (X² = 8.33, p = 0.016). The other variables show there is no significant difference in data and the p-value > 0.05. For successful passing (X² = 2.75, p = 0.253), for unsuccessful passing (X² = 5.79, p = 0.055), for shot on target (X² = 1.64, p = 0.440), and for scoring (X² = 1.15, p = 0.564). Moreover, the present study revealed that the significant difference was only found in shots off-target. Other than this, the variables show that there are no significant differences. This is because the effectiveness of a team’s attacking force in scoring goals is largely determined by its formation, player characteristics, and shooting abilities. Other than that, this team’s style of play emphasizes precise ball possession and methodical attacks, a formula that has been instrumental in their domestic and European triumphs. In conclusion, there is a significant difference in the shot-off target. But there is no significant difference in successful passing, unsuccessful passing, shot on target, and scoring.